Telluric absorption lines in the ALMA spectra of η Car. Issue 1 (19th September 2022) - Abraham, Zulema; Beaklini, Pedro P B; Cox, Pierre; Falceta-Gonçalves, Diego; Nyman, Lars-Åke
ABSTRACT: The massive binary system formed by η Car and an unknown companion is a strong source at millimetre and submillimetre wavelengths. Close to the stars, continuum bremsstrahlung and radio recombination lines originate in the massive ionized wind of η Car and in several compact sources of high density plasma. Molecular lines are also detected at these wavelengths, some of them are seen in absorption towards the continuum emission region, many of them revealed by ALMA observations. However, because the ALMA atmospheric calibration is performed in a low spectral resolution mode, telluric lines can still be present in some high-resolution spectra of scientific products, which could lead to a false identification of molecules. In this work, we explore three different sets of ALMA archive data of η Car, including high resolution (0.065 arcsec × 0.043 arcsec) observations recently published by our group, to verify which of these absorption lines are real and discuss their origin. We conclude that some of them truly originate in clouds close to the binary system, while others are artefacts of a faulty elimination of telluric lines during ALMA calibration procedure. We found that these absorption lines are not present in the phase calibrators because they are much weaker than η Car, where the absorption line appears because the high intensity continuum enhances the small individual systematic calibration errors.